2003
DOI: 10.1103/physrevlett.90.203201
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Collision Cross Sections for Low Energy Electron Scattering from NO: The Role of Resonances in Elastic Scattering and Vibrational Excitation

Abstract: Absolute measurements of elastic scattering and vibrational excitation of the NO molecule by low energy electron impact (0.4-2.5 eV) are presented. They show that previous estimates of these cross sections may be in error by as much as a factor of 3 and provide compelling evidence for a reassessment of the balance between elastic scattering and vibrational excitation at incident energies below 2 eV. They also confirm the critical contribution that intermediate negative ion resonances (NO-) make to the various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 14 publications
(19 reference statements)
7
47
1
Order By: Relevance
“…However, in contrast to what was seen in earlier experiments [8], we do not find a complete supression of the lowest few peaks in cross sections for exciting higher vibrational levels, but instead find encouragingly good agreement with the recent experiments of Allan [9,13].…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…However, in contrast to what was seen in earlier experiments [8], we do not find a complete supression of the lowest few peaks in cross sections for exciting higher vibrational levels, but instead find encouragingly good agreement with the recent experiments of Allan [9,13].…”
Section: Discussioncontrasting
confidence: 57%
“…In the case of elastic scattering, there is excellent agreement bewteen the two sets of measurements above 0.8 eV, whereas the peak cross sections values near 0.45 eV and 0.6 eV measured by Allan [9,13] are relatively larger than those measured by Jelisavcic et al [8]. The agreement with theory is also rather good, the principal difference being a somewhat larger value for the background cross section given by theory.…”
Section: A Elastic Scattering and Vibrational Excitationsupporting
confidence: 64%
See 2 more Smart Citations
“…[3] After new results for the cross sections of low-energy electron impact vibrational excitation of NO were obtained by swarm [Josić et al, 2001] and binary collision experiments [Jelisavcic et al, 2003], it was shown in an equilibrium calculation [Campbell et al, 2004] that such excitation could account for a significant part of the auroral NO infrared emission at a height of 120 km, assuming the NO density to be the maximum seen in observations. Here we revisit the subject for two reasons.…”
Section: Introductionmentioning
confidence: 99%